2019
DOI: 10.1111/nep.13493
|View full text |Cite
|
Sign up to set email alerts
|

Lime powder regimen supplement alleviates urinary metabolic abnormalities in urolithiasis patients

Abstract: LPR is a potential drug to correct urinary metabolic disorders associated with urolithiasis in high risk stone recurrent patients. A phase 3 clinical trial is underway to validate anti-stone recurrence property of LPR in long-term treatment. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Thus, Wattanachai et al . [ 15 ], found that potassium citrate supplementation significantly increased urinary pH and urinary potassium citrate excretion. Taken together, these data suggest that citrate salt can be used as a treatment option in patients with urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Wattanachai et al . [ 15 ], found that potassium citrate supplementation significantly increased urinary pH and urinary potassium citrate excretion. Taken together, these data suggest that citrate salt can be used as a treatment option in patients with urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lime powder inhibits COM crystal growth and prevents reactive oxygen species overproduction in COM crystal–induced tubular cell injury [ 106 ]. Clinical trial in healthy volunteers has revealed that lime powder enhances urinary citrate excretion, increases urine pH, and decreases urinary CaOx supersaturation [ 107 ]. Interestingly, there is no toxic effect of lime powder observed in in vitro cell culture, in vivo mice model, and healthy individuals, suggesting that lime powder should be safe for daily consumption [ 106 ].…”
Section: Strategies To Prevent Ksdmentioning
confidence: 99%